2016
DOI: 10.3329/bjvm.v14i1.28831
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemistry, Toxicity and in Vitro Antitrypanosomal Efficacy of Crude Aqueous Extract of Guiera Senegalensis Stem Bark

Abstract: The crude aqueous extract of Guiera senegalensis stem bark was evaluated for its phytochemistry, acute toxicity and in vitro antitrypanosomal efficacy in this study. Tests for alkaloids, flavonoids, tannins, phlabotannins, saponins, steroids, cardenolides, terpenoids, cardiac glycosides, and anthraquinones were conducted. A total of 15 albino rats of both sexes were used and grouped into 5 (A to E) of 3 rats each. Groups A-D were intraperitoneally treated with graded doses of 100, 200, 400, 800mg/kg body weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
0
3
0
4
Order By: Relevance
“…Le criblage phytochimique des extraits de feuilles, de racines, de tiges et de galles a montré la présence d'hydrates de carbone, de stéroïdes, de saponines, de flavonoïdes, d'alcaloïdes, de tanins, de saponines, de glycosides cardiaques, de coumarines, d'anthraquinones, d'acide ascorbique, d'hétérosides cardiotoniques, de cyanogènes et de terpénoides (Sule et al, 2001;Lamien et al, 2005;Williams et al, 2009;Sombié et al, 2011;Somboro et al, 2011;Mamman et Isa, 2013;Salihu et Usman, 2015;Al Shafei et al, 2016;Biu et al, 2016). Mariod et al (2016) ont déterminé, selon la procédure de Folin-Ciocalteu et calculée en équivalents d'acide gallique (EAG), les teneurs en composés phénoliques totaux dans les extraits de feuilles.…”
Section: Composition Chimiqueunclassified
See 2 more Smart Citations
“…Le criblage phytochimique des extraits de feuilles, de racines, de tiges et de galles a montré la présence d'hydrates de carbone, de stéroïdes, de saponines, de flavonoïdes, d'alcaloïdes, de tanins, de saponines, de glycosides cardiaques, de coumarines, d'anthraquinones, d'acide ascorbique, d'hétérosides cardiotoniques, de cyanogènes et de terpénoides (Sule et al, 2001;Lamien et al, 2005;Williams et al, 2009;Sombié et al, 2011;Somboro et al, 2011;Mamman et Isa, 2013;Salihu et Usman, 2015;Al Shafei et al, 2016;Biu et al, 2016). Mariod et al (2016) ont déterminé, selon la procédure de Folin-Ciocalteu et calculée en équivalents d'acide gallique (EAG), les teneurs en composés phénoliques totaux dans les extraits de feuilles.…”
Section: Composition Chimiqueunclassified
“…Une autre étude plus récente rapporte l'activité antitrypanosomique in vitro de l'extrait aqueux brut d'écorces de tige de G. senegalensis. L'efficacité antitrypanosomique in vitro de l'extrait a montré une inhibition de 100% de la motilité contre Trypanosoma brucei à 20 mg/ml (Biu et al, 2016).…”
Section: Activité Antiparasitaireunclassified
See 1 more Smart Citation
“…studies, as shown in Table 7, to possess healing properties against many diseases [20] including cough, respiratory congestion, fever [19] bronchial disorders [13], stomach pains and dysenteric diarrhoea [21] and malaria [22]. Adapted from Alshafei et al [19] These healing properties, as reported by these studies among others, therefore prompted the present investigation into its phytochemical constituents as well its activity against malaria parasite; Plasmodium berghei Strain ANKA in Wister albino rats.…”
Section: Ijppe Volume 13mentioning
confidence: 99%
“…These natural remedies have now dominated primary health care in over 80% of the world population [8]. Guiera senegalensis, also known as "Sabara" (in the Hausa language) and "Kishishi" (in Kanuri language) has now been used in traditional medicine for the treatment of many diseases including cough, respiratory congestion and fever [9]. Aniagu et al [10] used extracts of this plant's leaves, branches, bark and roots for the treatment of stomach pains and dysentery, while its use in the treatment of syphilis, beriberi, leprosy and impotence has also been reported [11].…”
Section: Introductionmentioning
confidence: 99%